VOLATILITY SHOCK PERSISTENCE IN INVESTMENT DECISION MAKING: A COMPARISON BETWEEN THE CONSUMER GOODS AND PROPERTY-REAL ESTATE SECTORS OF THE INDONESIAN CAPITAL MARKET - Ari Christianti (Faculty of Economics and Business, Universitas Gadjah Mada, 2018)
Research about volatility shock persistence is very important, since it could reflect the risks that can be used to estimate the fluctuations of stock returns in the future. This paper investigates a comparison of the volatility shock persistence sectoral indexes between the consumer goods (CONS) and property-real estate (PROP) sectors, using a single index model analyzed using GARCH (Generalized Autoregressive Conditional Heteroscedasticity) and I-GARCH (Integrated-Generalized Autoregressive Conditional Heteroscedasticity). By using index return data from January 2010-December 2015, the research shows that CONS and PROP tend to produce the same results. The CONS and PROP indexes’ responses to volatility shocks tended to be quite fast. Hence, the single index model of the CONS and the PROP indexes can quickly return to its normal stability. It means that, in the presence of certain information which could affect the volatility of the return from these sectors, the market will respond and adapt immediately. This might be attributed to the fact that CONS is a sector that involves fast moving products. Furthermore, the PROP sector has an indirect effect by increasing the real sectoral economic activity and economic growth in Indonesia, which has a large population. Thus, it is recommended that investors who are risk averse and risk neutral should invest in these sectors, because the volatility of both indexes can be monitored based on the existing information.